An integrated electrocoagulation – Electrocatalysis water treatment process using stainless steel cathodes coated with ultrathin TiO2 nanofilms. (September 2020) - Fan, Tianzhu; Deng, Wei; Feng, Xuhui; Pan, Fuping; Li, Ying
Abstract: Anodic electrocoagulation processes can remove broad varieties of pollutants in industrial wastewater. However, some stubborn contaminants may still remain in effluents after the treatment and cause environmental issues. To further improve the efficiency of pollutant removal, we have coupled electrocatalysis with electrocoagulation and applied an atomic layer deposition (ALD) enabled TiO2 ultrathin overcoating at a nanometer scale on a stainless steel cathode. The electrocatalytic overcoating increased the elimination efficiency of organics and microorganisms, likely due to the electro-generation of adequate reactive oxygen species (ROS). The thickness of TiO2 nanofilm was controlled by the number of ALD cycles, and it was found that nanofilms processed with 50–100 cycles led to the maximum benefit of pollutant removal. By using the novel electrocoagulation–electrocatalysis cell to treat synthetic wastewater, a remarkable removal of 99.92% of E. Coli, 92.1% of suspended solids, 98.3% of heavy metal ions, and 88.8% of methylene blue was observed. This hybrid electrochemical treatment process may have the potential to treat wastewater at a larger scale. Graphical abstract: Image 1 Highlights: A novel electrocoagulation-electrocatalysis cell was designed for wastewater treatment. The system consists of Al anode and SS mesh cathode coated with ALD-TiO2 nanofilm. The TiO2 nanofilm enhanced the removal efficiency without extra power consumption. Efficient removal of organics, bacteria, heavy metals, and suspended solids was achieved.